2018
DOI: 10.1053/j.gastro.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Determining Risk of Barrett’s Esophagus and Esophageal Adenocarcinoma Based on Epidemiologic Factors and Genetic Variants

Abstract: We used data from 3 large databases of patients from studies of BE or EAC to develop a risk prediction model based on genetic, clinical, and demographic/lifestyle factors. We identified a PRS that increases discrimination and net reclassification of individuals with vs without BE and EAC. However, the absolute magnitude of improvement is not sufficient to justify its clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 40 publications
4
66
0
Order By: Relevance
“…These tools may require the addition of noninvasive genetic or blood biomarkers to demographic and historical variables to improve the areas under the receiver operating characteristic curves and overall performance. 117 Before we embrace the new generation of less-invasive and potentially less-expensive screening techniques and replace our current approach of using standard endoscopy for screening, these new techniques need to demonstrate high diagnostic performance characteristics, easy implementation at a primary care level, high uptake in the at-risk population, and low cost. 118 Future studies also need to focus on improved risk stratification of BE patients undergoing surveillance with the intent of performing EET for high-risk populations and extending or discontinuing surveillance in low-risk groups.…”
Section: Future Directionsmentioning
confidence: 99%
“…These tools may require the addition of noninvasive genetic or blood biomarkers to demographic and historical variables to improve the areas under the receiver operating characteristic curves and overall performance. 117 Before we embrace the new generation of less-invasive and potentially less-expensive screening techniques and replace our current approach of using standard endoscopy for screening, these new techniques need to demonstrate high diagnostic performance characteristics, easy implementation at a primary care level, high uptake in the at-risk population, and low cost. 118 Future studies also need to focus on improved risk stratification of BE patients undergoing surveillance with the intent of performing EET for high-risk populations and extending or discontinuing surveillance in low-risk groups.…”
Section: Future Directionsmentioning
confidence: 99%
“…Prior studies have identified male gender, increasing age, obesity, and, most importantly, chronic gastroesophageal reflux disease (GERD) as the risk factors associated with the development of Barrett's esophagus (BE). 1 Chronic exposure of the distal esophageal mucosal lining to acid reflux induces metaplastic change, which then predisposes the individual to the development of esophageal adenocarcinoma. BE is a mostly asymptomatic condition, and given its potential for malignant transformation, it is usually diagnosed by screening populations at high risk.…”
Section: Introductionmentioning
confidence: 99%
“…Risk models incorporating both genetic and nongenetic factors have previously been developed for predicting risks of various cancers. However, recent studies from our working group and others have found that adding inherited genetic information to a risk model using only clinical and lifestyle factors did not improve discriminatory ability for predicting oesophageal cancer development in the general population . Future research should assess whether or not genetic factors or somatic mutations may improve discrimination in the setting of neoplastic progression in Barrett's oesophagus patients.…”
Section: Discussionmentioning
confidence: 88%
“…Multiple risk models have been derived (and some externally validated) for predicting Barrett's oesophagus and oesophageal adenocarcinoma . However, few models exist in the setting of risk prediction among patients with Barrett's oesophagus.…”
Section: Discussionmentioning
confidence: 99%